Ultra-wideband RF system engineering - Zwick, Thomas; Wiesbeck, W. (EuMA high frequency technologies series., 2013)
"This comprehensive summary of the state of the art in Ultra Wideband (UWB) system engineering takes you through all aspects of UWB design, from components through the propagation channel to system engineering aspects. Mathematical tools and basics are covered, allowing for a complete characterisation and description of the UWB scenario, in both the time and the frequency domains. UWB MMICs, antennas, antenna arrays, and filters are described, as well as quality measurement parameters and design methods for specific applications. The UWB propagation channel is discussed, including a complete mathematical description together with modeling tools. A system analysis is offered, addressing both radio and radar systems, and techniques for optimization and calibration. Finally, an overview of future applications of UWB technology is presented. Ideal for scientists as well as RF system and component engineers working in short range wireless technologies"--